From authoritarianism to Europeanization? Paths to a contestable European future in Greece and Poland - Lavdas, Kostas A.; Kotroyannos, Dimitrios; Tzagkarakis, Stylianos Ioannis (2017)
Abstract: The paper aims to explore Europeanization paths, outcomes and prospects in Greece and Poland, focusing on comparative interactions between regime transformation, interest politics and accession processes. The interactions in question involve (a) influences of politics, institutional traditions and interests on the formation of the applicant states’ European strategy and (b) interactions between processes of integration and organized interests and domestic political contestation. Interactions work in the context of more general Europeanization processes, which concern adaptation, adjustment, impact and feedback, beginning in anticipation of membership and expanding to more synchronized if still asymmetrical developments during later stages of full membership. Different paths from authoritarianism to democracy have combined with different Europeanization processes to result in partial divergence in Europeanization outcomes